Effects of Laser Polishing on Surface Roughness and Corrosion Properties on Laser Welds as Post-Treatment - Väisänen, Inka; Tourunen, Eter; Tarson, Kristina; Kamboj, Nikhil; Piili, Heidi; Salminen, Antti (United Kingdom, 2026)
Materials used in maritime industries suffer from severe corrosion due to constant exposure to saltwater and harsh marine environments. Welds in metals are particularly prone to corrosion, leading to mechanical failure and structural degradation of ships and larger vessels. Laser polishing is an effective technique that redistributes molten material into cavities, smoothing the weld surface and enhancing longevity. Aim of this study was to examine the effects of laser polishing on marine grade EH36 steel welds, focusing on corrosion resistance and surface roughness. Laser polishing was performed using an IPG nanosecond pulsed fiber laser with a maximum average power of 100W and a wavelength range of 1055-1075 nm (typically 1064 nm). Samples were polished from the top and root sides of the weld. Corrosion properties were tested using an Ivium electrochemical analyser and a Gamry instruments surface corrosion system, while surface inspection and roughness values were obtained with a Bruker Alicona Infinite Focus G6. The steel surface underwent six treatment cycles with a scanning speed of 450 mm/s and a pulse frequency of 100 kHz. Optimal results were achieved at a laser power of 75 W and a pulse width of 25 ns. Laser polishing decreased areal average roughness Sa by about 65 % compared to non-laser polished surfaces. Additionally, the corrosion rate of the top surface of the laser-polished sample showed a substantial reduction of 94 % compared to the non-laser polished weld. The root surface corrosion rate increased 33 % which suggests a significant difference between the root and top surfaces of welds. These findings suggest that laser polishing effectively smooths weld surfaces, leading to improved durability, reduced maintenance requirements, and extended service life of marine structures and ships.
20th Nordic Laser Materials Processing Conference